Metatranscriptomics of the Hu sheep rumen microbiome reveals novel cellulases - Bo He; Shuwen Jin; Jiawen Cao; Lan Mi; Jiakun Wang (Biotechnology for Biofuels, 2019)
Abstract Background Cellulosic biomass has great potential as a renewable biofuel resource. Robust, high-performance enzymes are needed to effectively utilize this valuable resource. In this study, metatranscriptomics was used to explore the carbohydrate-active enzymes (CAZymes), especially glycoside hydrolases (GHs), present in the rumen microbiome of Hu sheep. Select CAZymes were experimentally verified and characterized after cloning and expression in E. coli. Results The metatranscriptomes of six Hu sheep rumen microbiomes yielded 42.3 Gbp of quality-checked sequence data that represented in total 2,380,783 unigenes after de novo assembling using Trinity and clustered with CD-HIT-EST. Annotation using the CAZy database revealed that 2.65% of the unigenes encoded GHs, which were assigned to 111 different CAZymes families. Firmicutes (18.7%) and Bacteroidetes (13.8%) were the major phyla to which the unigenes were taxonomically assigned. In total, 14,489 unigenes were annotated to 15 cellulase-containing GH families, with GH3, GH5 and GH9 being the predominant. From these putative cellulase-encoding unigenes, 4225 open reading frames (ORFs) were predicted to contain 2151 potential cellulase catalytic modules. Additionally, 147 ORFs were found to encode proteins that contain carbohydrate-binding modules (CBMs). Heterogeneous expression of 30 candidate cDNAs from the GH5 family in E. coli BL21 showed that 17 of the tested proteins had endoglucanase activity, while 7 exhibited exoglucanase activity. Interestingly, two of the GH5 proteins (Cel5A-h28 and Cel5A-h11) showed high specific activity against carboxymethylcellulose (CMC) and p-nitrophenyl-β-d-cellobioside (pNPC) (222.2 and 142.8 U/mg), respectively. The optimal pH value for activity of Cel5A-h11 and Cel5A-h28 was 6.0 for both enzymes, and optimal temperatures were 40 and 50 °C, respectively. Both enzymes retained over 70 and 60%, respectively, of their original activities after incubation at 40 °C for 60 min. However, their activities were rapidly diminished upon exposure to higher temperatures. Cel5A-h11 and Cel5A-h28 retained more than 80 and 60% of their maximal enzymatic activities after incubation for 16 h in buffered solutions in the pH range from 4.0 to 9.0. Conclusion The metatranscriptomic results revealed that the rumen microbiome of Hu sheep encoded a repertoire of new enzymes capable of cellulose degradation and metatranscriptomics was an effective method to discover novel cellulases for biotechnological applications.